Tsunami Forecasting Due to Seismic Activity in Manila Trench of Malaysia Offshore Oil Blocks - ., NH Mardi, MS Liew, MA Malek, MN Abdullah (2015)
Manila Trench is a potential generation source of tsunami in the South China Sea. Manila Trench is formed when Eurasian Plate is subducted under the Philippine Sea Plate. It has been classified as the most hazardous tsunami sources in USGS Tsunami Sources Workshop, 2006. The location of the trench begins at the north of Palawan, Philippines, continuing to the north along the west of Luzon, Philippine, and ends at Taiwan. The potential tsunami generated from Manila Trench affects Philippines and countries located in the vicinity of South China Sea including Malaysia. This chapter focuses on simulation of tsunami generation and tsunami wave propagation due to seismic activity in the Manila Trench. TUNA-M2 model is used to produce simulation results in terms of tsunami wave height and time of arrival of the first wave. The study area is Malaysian offshore reserves and operation where oil and gas platforms are located. There are three simulations performed at different moment magnitudes (Mw: 7.0, 7.5, and 8.0). The result shows the range of wave heights at the Malay basin to be between 0.002 and 0.122 m, the range of wave heights at Sabah basin to be between 0.004 and 0.168 m, and the range of wave heights at Sarawak basin to be between 0.004 and 0.230 m. These results are useful in the future design of offshore platform structure and operation